You are who your friends are: An experiment on trust and homophily in friendship networks - Mitesh Kataria; Fabian Winter (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
We study the existence of homophily (i.e. the tendency for people to make friends with people who are similar to themselves) with respect to trustworthiness. We ask whether two friends show similarly trustworthy behavior towards strangers, and whether this is anticipated by outsiders. We develop a simple model of bayesian learning in trust games and test the derived hypotheses in a controlled laboratory environment. In the experiment, two trustees sequentially play a trust game with the same trustor, where the trustees depending on treatmen are either friends or strangers to each other. We affirm the existence of homophily with respect to trustworthiness. Trustors beliefs about the trustees trustfulness are not affected by the knowledge about the (non-)existent friendship between the trustees. Behaviorally, however, they indirectly reciprocate the (un-)trustworthy behavior of one trustee towards his/her friends in later interactions.
Keywords: C92; D83; J24; J40; 330; friendship; homophily; indirect tit-for-tat; social networks; trust